Does atorvastatin work more effectively than biguanides in reducing cardiovascular risk factors? - Afshan Siddiq; Rafeeq Alam Khan; Sadia Ghousia Baig (Wolters Kluwer Medknow Publications, 2011)
Increased risk of coronary artery disease in diabetic persons is associated with increased level of lipoproteins. Usually, such risks are reverted with glycemic control by antidiabetic medicines in Type I diabetes millitus. However, in Type II diabetes mellitus lipid values can be improved using antidiabetics but still the risk of coronary artery disease remains. The initial approach for reducing lipid contents in diabetic patients should include glycemic control, diet, weight loss, and exercise. But if it fails then lipid-lowering agents like fibrate and HMG CoA reductase (3-hydroxy-3-methyl-glutaryl-CoA reductase) inhibitors should work effectively. In the present study results of atorvastatin compared with biguanides proved atorvastatin as a more effective lipid-lowering agent along with antidiabetic activity so it can effectively help in reducing the risk of cardiovascular disease (CVD).